Study of addictions formation in foreignsocio-psychological concepts (The Journal of Psychology and Sociology, 2016)
The article presents review of foreign socio-psychological theories of the drug addiction development: social learning theory or social cognitive theory (Bandura), social networks theory (Needle) and social influence theory (Ling), stages of be-havior change theory (Prochaska, DiClemente), health belief model (Rosenstock), social control theory (Elliot), the social development model (Hawkins, Weis), family interaction theory (Brook), problem behavior theory (Jessor). Most researchers in the socio-psychological approach to address the factors of drug addiction among young people focus on the characteristic of the social environment. Scientists, ex-perts working in the field of prevention of various forms of addictive behavior, pay great attention to the study of social and psychological factors in the formation of drug addiction. The success of a variety of prevention and rehabilitation programs for drug use is largely based on the socio-psychological determinants of human be-havior. Important role in explaining the formation of drug addiction played a theory, emphasizing the importance of interpersonal relationships in the spread of a form of behavior.Social learning theory suggests that mediated experience is an important part of the expectations of efficiency, and this position predicts steady positive effect of attracting peers for educational purposes for the prevention of alcohol and drug abuse. The social theories of motivation are six main stages through which individu-als in the process of changing their behavior. The theory of behavioral change stages used by Russian specialists, in particular in the organization of work on prevention of drug addiction among college students.
Keywords: personality factors; the social environment; referent group; risk; drug use; psychoactive substances.